Rare presentation of TB oesophagus: a case report - Reddy, Nagella Pradeep Kumar; Jeyasekharan, S. Sabu; C., Nithila; Kishore, A. Sai (International Surgery Journal, 2018)
This is a rare case report of Tb oesophagus presenting as upper GI bleeding. Patient was subjected to upper gastrointestinal endoscopy, which revealed an ulcerative growth in the mid oesophagus. Biopsy revealed oesophageal tuberculosis. Patient was managed conservatively with Anti-Tuberculosis Treatment (ATT). Follow up endoscopy after six months revealed resolution of the ulcer and patient was symptomatically better. In spite of the rare nature of the disease, it can be managed effectively with ATT to avoid complications (fistula, stricture, and oesophageal perforation), which might warrant surgery.